Description of Histopona breviemboli sp. n. from the Balkan Peninsula (Arachnida, Araneae, Agelenidae) - Dimitrov, Dragomir; Deltshev, Christo; Lazarov, Stoyan (Zootaxa, 2017)
Histopona breviemboli sp. nov. (male) is described and illustrated from Bulgaria where it was collected in beech forest habitats (Strandzha Mts). The new species has somatic characters that correspond well to those of the genus Histopona. However, its embolus is much shorter than in any other Histopona species and the radix is also very different, having a thorn-like shape. The species cannot be placed with certainty in any of the existing Histopona species-groups.